Fundamental Analysis of Financial Ratios in Stock Price: Do Loss and Firm Size Matter? - Siti Nur Aini; Adib Minanurohman; Nurul Fitriani (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2023)
Purpose: This study aims to examine the relationship between financial ratios and stock price, and we further test the variables in the subsamples of loss or profit and the firm size.Method: This study used non-financial companies listed on Indonesia Stock Exchange (IDX) from 2010-2020.Findings: The result shows that all financial ratios used in this study are positively associated with the stock price, except the solvability ratio is negatively associated with the stock price. Furthermore, in the subsample of companies that experience losses, only a few financial ratios have a relationship with stock prices. Then, the companies that have a small size show an insignificant liquidity ratio. This result is robust using coarsened exact matching (CEM).Novelty: The results add to the literature regarding the ability of financial ratios to stock prices and especially provide new evidence from loss or profit and the firm size in Indonesia.